Management of Multidrug Resistant Tuberculosis - Daley, Charles L.; Caminero, Jose A. (Seminars in Respiratory and Critical Care Medicine, 2013)
Drug-resistant strains of Mycobacterium tuberculosis have emerged as a major threat to global tuberculosis control. Despite the availability of curative antituberculosis therapy for nearly half a century, inappropriate and inadequate treatment has allowed M. tuberculosis to acquire resistance to our most important antituberculosis drugs. The epidemic of drug-resistant tuberculosis has spread quickly in some areas due to the convergence of resistant strains of M. tuberculosis in high-risk patients (e.g., those with human immunodeficiency virus/acquired immunodeficiency syndrome) and high-risk environments (e.g., hospitals and prisons). The World Health Organization (WHO) estimates that there were 650,000 cases of multidrug resistant tuberculosis (MDR-TB) in 2010, defined as strains that are resistant to at least isoniazid (INH) and rifampicin (RIF). Globally, WHO estimates that 3.7% of new tuberculosis cases and 20% of re-treatment cases have MDR-TB. By the end of 2012, 84 countries had reported at least one case of extensively drug resistant strains (XDR-TB), which are MDR-TB strains that have acquired additional resistance to fluoroquinolones and at least one second-line injectable. Recently, cases of “totally drug resistant” tuberculosis have been reported. It is estimated that only 10% of all MDR-TB cases are currently receiving therapy and only 2% are receiving quality-assured drugs. This article reviews the management of MDR and XDR-TB and highlights the updated 2011 WHO guidelines on the programmatic management of drug-resistant tuberculosis.
Keywords: tuberculosis; drug resistant; MDR-TB; XDR-TB; management